2003
DOI: 10.1161/01.cir.0000055323.57885.88
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic Iron Oxide–Based Method for Quantifying Recruitment of Monocytes to Mouse Atherosclerotic Lesions In Vivo

Abstract: Background-It has been found recently that the MRI contrast agent superparamagnetic iron oxide (SPIO) localizes to aortic atherosclerotic plaques. We therefore asked whether SPIO might be used to monitor monocyte recruitment into aortic atherosclerotic plaques. Methods and Results-Eleven female apo E knockout (K/O) mice, each 11 months old, were divided into 2 groups. Six mice received tissue necrosis factor-␣ (0.2 g IP once), interleukin-1␤ (0.2 g IP once), and interferon-␥ (100 U/g per day IP for 5 days); 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 14 publications
4
66
0
Order By: Relevance
“…Additionally, superparamagnetic iron oxide (SPIO) has been used to quantify monocyte recruitment histologically in atherosclerotic lesions of the apolipoprotein E-deficient (apoE Ϫ/Ϫ ) mouse. 15 In that study, acute administration of tumor necrosis factor (TNF), interleukin (IL)-1␤, and interferon (INF)-␥ was shown to stimulate SPIO uptake by 4-fold in plaque. Although this study supports the hypothesis that plaque targeting of the USPIO contrast agent in mouse is facilitated by monocyte recruitment or activation of macrophage phagocytosis, noninvasive assessment of USPIO uptake in mouse atherosclerotic lesions has not been reported.…”
Section: Methods and Results-apoementioning
confidence: 98%
“…Additionally, superparamagnetic iron oxide (SPIO) has been used to quantify monocyte recruitment histologically in atherosclerotic lesions of the apolipoprotein E-deficient (apoE Ϫ/Ϫ ) mouse. 15 In that study, acute administration of tumor necrosis factor (TNF), interleukin (IL)-1␤, and interferon (INF)-␥ was shown to stimulate SPIO uptake by 4-fold in plaque. Although this study supports the hypothesis that plaque targeting of the USPIO contrast agent in mouse is facilitated by monocyte recruitment or activation of macrophage phagocytosis, noninvasive assessment of USPIO uptake in mouse atherosclerotic lesions has not been reported.…”
Section: Methods and Results-apoementioning
confidence: 98%
“…MRI capabilities may be enhanced with the use of agents to enhance contrast of macrophage presence. 62 Novel agents have been developed for MR (and near-infrared [NIR]) molecular imaging that are activated by local enzymatic processes. 63 Strauss et al 64 have noted that the ability of nuclear studies to detect metabolic activity may eventually lead to successful noninvasive studies of vulnerable coronary artery plaques.…”
Section: Noninvasive Methods To Image Vulnerable Plaques In the Coronmentioning
confidence: 99%
“…This is a general observation, and again it must be stressed that many factors can and will influence the pattern as well as quantity of USPIO particle uptake by plaque including, animal model, plaque location, and USPIO dosing paradigm. In another study examining Feridex deposition in atherosclerotic plaque of apoE Ϫ/Ϫ mice treated with a proinflammatory cytokine cocktail, Litovsky et al 7 showed iron deposition to be largely intracellular and associated with subendothelial macrophages as well as occasionally found in deeper regions adjacent to the internal elastic lamina. We have also found general colocalization of the Perl's staining with regions associated with macrophages ( Figure, D).…”
Section: In Responsementioning
confidence: 99%